Isolasi Bakteri Penghasil Enzim Lipase Penghasil Alkali dari Kulit Hewan - V.S. Pertiwi Rumiyati; Retno Indrati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1998)
Twenty seven bacterial strains isolated an a medium containing 0.50% palm oil as substrate and 0.015% spirit blue as an indicator from several raw hides of chicken, goat and cow showed an extracellular lipase activity. Of these strains, 10 were higher lipase producers. Lipases produced from five of these 10 isolates were stable on alkaline conditions, ranging from pH 8.0 to 11.0. Furthermore, activity of these enzymes was not inhibited by the presence of non-ionic, cationic nor ionic surfactants at concentration of 0.05% or 0.10%. Conversely, some of these surfactans could even activate the enzyme.